IN-HOSPITAL DIURETIC USE IS ASSOCIATED WITH WORSE OUTCOME IN PATIENTS WITH COVID-19. (April 2021) - Pengo, M.; Stefanini, G; Pivato, C; Soranna, D; Zambra, G; Zambon, A; Torlasco, C; Bilo, G; Condorelli, G; Parati, G
Abstract : Objective: Background: Hypertension is associated with increased risk of severe COVID-19 and increased mortality. The knowledge about the impact of blood pressure lowering medications on outcomes is still incomplete: whilst studies about renin-angiotensin-aldosterone system inhibitors did not show association with increased mortality, less is known about the impact of other antihypertensive classes. Diuretics, in particular, are frequently used in patients with hypertension thus we aimed to investigate the association between diuretics and mortality in a cohort of COVID-19 patients hospitalized in two referral centers in the Lombardy region (Istituto Auxologico Italiano and Humanitas Research Hospital). Methods: Data of confirmed COVID-19 patients, with information available about drug treatment and outcomes, were pooled together. Socio-demographic, clinical features, and medications pre and during hospitalization were retrieved, patients were classified according to the use of diuretics before and/or during hospitalization. The effect of diuretic use before and during hospitalization on death was estimated by means of a multiple Poisson regression model with robust variance and reported as Relative Risk (RR) and 95% confidence interval (95% CI). Design and method: From the pooled sample of 637 patients, a final sample of 502 patients with complete data was analyzed (mean age 67 years, 67% males, 54% patients with hypertension). Among hypertensive patients, 64% were not treated with diuretics either pre- or during hospitalization (Reference group), 15% had diuretic treatment only during hospitalization (Group A), 9% only pre-hospitalization (Group B) and 12% both pre- and during hospitalization (Group C). After adjusting for confounders (age, sex, respiratory rate at admission, number of comorbidities, number of other drugs taken during hospitalization, orotracheal intubation), use of diuretics only during hospitalization was significantly associated with mortality (Figure 1). Conclusion: Our data show an association between diuretic use only during hospitalization and worse outcome in patients with COVID-19. Such association needs to be further investigated in order to possibly improve outcomes in patients admitted for COVID-19 Figure. No caption available. Figure 1: Relative Risks and 95% confidence intervals of patients treated with diuretics only during hospitalization (Group A), only during pre-hospitalization (Group B) and during both pre- and hospitalization (Group C). The subgroup of patients not treated with diuretics neither pre- nor during hospitalization was taken as the reference group.